Chemotherapy in patients with early breast cancer: clinical overview and management of long-term side effects. Issue 11 (2nd November 2022) - Di Nardo, Paola; Lisanti, Camilla; Garutti, Mattia; Buriolla, Silvia; Alberti, Martina; Mazzeo, Roberta; Puglisi, Fabio
ABSTRACT: Introduction: Neo/adjuvant therapy for early-stage breast cancer has become increasingly common in the last few decades; as a consequence, the number of breast cancer survivors experiencing often debilitating long-term side effects has increased, and thus the need for a comprehensive approach to the variety of symptoms involved. Areas covered and methods: We performed a literature search on the main public scientific databases (PubMed, Embase, Cochrane, and CrossRef) from 2000 to April 2022 to identify prevention and management strategies for the most common long-term side effects, including fatigue, insomnia, peripheral neuropathy, cognitive impairment, estrogen deprivation, cardiotoxicity, and second cancers. Expert opinion: Long-term toxicities may affect a majority of breast cancer survivors, significantly interfering with their quality of life. Although there are guidelines for the management of isolated side effects, such as peripheral neuropathy, we aim to provide a more inclusive clinical-oriented approach, focusing on both prevention and therapeutic strategies